Efficient Dense Stereo with Occlusion for New View-Synthesis by Four-State Dynamic Programming - Criminisi, Antonio; Shotton, Jamie; Blake, Andrew; Rother, Carsten; H.S. Torr, Philip (2007)
A new algorithm is proposed for efﬁcient stereo and novel view synthesis. Given the video streams acquired by two synchronized cameras the proposed algorithm synthesises images from a virtual camera in arbitrary position near the physical cameras. The new technique is based on an improved, dynamic-programming, stereo algorithm for efﬁcient novel view generation. The two main contributions of this paper are: i) a new four state matching graph for dense stereo dynamic programming, that supports accurate occlusion labelling; ii) a compact geometric derivation for novel view synthesis by direct projection of the minimum cost surface. Furthermore, the paper presents an algorithm for the temporal maintenance of a background model to enhance the rendering of occlusions and reduce temporal artefacts (ﬂicker); and a cost aggregation algorithm that acts directly in the three-dimensional matching cost space. The proposed algorithm has been designed to work with input images with large disparity range, a common practical situation. The enhanced occlusion handling capabilities of the new dynamic programming algorithm are evaluated against those of the most powerful state-of-the-art dynamic programming and graph-cut techniques. Four-state DP is also evaluated against the disparity-based Middlebury error metrics and its performance found to be amongst the best of the efﬁcient algorithms. A number of examples demonstrate the robustness of four-state DP to artefacts in stereo video streams. This includes demonstrations of cyclopean view synthesis in extended conversational sequences, synthesis from a freely translating virtual camera and, ﬁnally, basic 3D scene editing.